2016
DOI: 10.1002/2015gb005355
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton size impact on export flux in the global ocean

Abstract: Efficiency of the biological pump of carbon to the deep ocean depends largely on biologically mediated export of carbon from the surface ocean and its remineralization with depth. Global satellite studies have primarily focused on chlorophyll concentration and net primary production (NPP) to understand the role of phytoplankton in these processes. Recent satellite retrievals of phytoplankton composition now allow for the size of phytoplankton cells to be considered. Here we improve understanding of phytoplankt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 68 publications
4
55
1
Order By: Relevance
“…In addition, satellite PG data were used to assess globally particulate organic carbon export (Mouw et al, 2016), for detection of regional HAB events (e.g., Kurekin et al, 2014), the estimation of recruitment of juvenile fish (Trzcinski et al, 2013) and for inferring globally oceanic emissions of volatile organic compounds (Arnold et al, 2009;Booge et al, 2016).…”
Section: Approachmentioning
confidence: 99%
“…In addition, satellite PG data were used to assess globally particulate organic carbon export (Mouw et al, 2016), for detection of regional HAB events (e.g., Kurekin et al, 2014), the estimation of recruitment of juvenile fish (Trzcinski et al, 2013) and for inferring globally oceanic emissions of volatile organic compounds (Arnold et al, 2009;Booge et al, 2016).…”
Section: Approachmentioning
confidence: 99%
“…This is evidenced by export efficiencies in the lower range (more of the net primary production is remineralized in the euphotic zone) at various open ocean locations with a considerable picophytoplankton contribution (for a review see De La Rocha and Passow, 2014). At a single location, however, during a seasonal cycle smaller assemblages, although not necessarily comprising picophytoplankton, can be associated with higher export efficiency than larger assemblages (Mouw et al, 2016).…”
Section: Implications For Future Biogeochemical Element Cyclingmentioning
confidence: 99%
“…The mechanisms behind such changes include phytoplankton species specific requirements and sensitivities for CO 2 and HCO − 3 , pH, inorganic nutrients, light and temperature, which in turn will influence community composition, a major factor shaping export efficiency, i.e., the ratio of carbon exported to the depth of the euphotic zone (<1% light penetration) to surface net primary production, and transfer efficiency in the deep ocean, i.e., the ratio of carbon reaching deeper layers to export production. Together, the attenuation of the organic carbon flux with depth and marine primary productivity ultimately determine the amount of atmospheric carbon locked away in the deeper ocean for timescales beyond decades (compare e.g., Buessler and Boyd, 2009;De La Rocha and Passow, 2014;Mouw et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant patterns of T EFF and its controlling factors are uncertain. Several studies have suggested that T EFF is positively related to ballasting by calcium carbonate and inversely related to surface export efficiency—defined as the ratio of particulate organic carbon export from the euphotic zone to net primary production (Siegel et al, )—resulting in highest T EFF in low latitude oligotrophic regions (Francois et al, ; Guidi et al, ; Henson et al, ; Lam et al, ; Mouw et al, ). A similar pattern would emerge if seasonal plankton blooms produce more labile organic matter, which is easier for microbes to break down in the mesopelagic zone (Lam et al, ).…”
Section: Introductionmentioning
confidence: 99%